Household herbicide use as a source of simazine contamination in urban surface waters. (15th April 2022) - Myers, Jackie H.; Rose, Gavin; Odell, Erica; Zhang, Pei; Bui, AnhDuyen; Pettigrove, Vincent
Abstract: Contamination of urban surface waters by herbicides is an increasing concern; however, sources of contamination are poorly understood, hindering the development of mitigation and regulatory strategies. Impervious surfaces, such as concrete in driveways and paths are considered an important facilitator for herbicide runoff to urban surface waters following applications by residential homeowners. This study assessed the transferability of a herbicide from concrete pavers treated with an off-the-shelf product, containing simazine as the active herbicide, marketed for residential homeowner application to impervious surfaces. Commercially available pavers were treated according to label directions and the effects of exposure time prior to irrigation, repeated irrigations, and dry time between irrigations on transferability of simazine to runoff were assessed. Simazine transferability was greatest when receiving an initial irrigation 1 h after application, with concentrations in runoff reduced by half when exposure times prior to the first irrigation were >2 days. Concentrations remained stable for repeated irrigations up to 320 days and exposures to outdoor conditions of 180 days prior to a first irrigation. Dry time between irrigations significantly influenced simazine transfer to runoff. Dry periods of 140 days resulted in approximately a 4-times increase in simazine transferability to runoff. These results suggest that herbicides used by homeowners, or any other users, on impervious surfaces are available to contaminate runoff for prolonged time periods following application at concentrations that may pose risks to aquatic life and for reuse of harvested runoff on parks and gardens. Regulators should consider the potential of hard surfaces to act as reservoirs for herbicides when developing policies and labelling products. Graphical abstract: Image 1 Highlights: Homeowner applied herbicides can contribute substantial emissions to surface waters. Increased dry times leads to increased herbicide transfer to runoff. Herbicide transfer is greatest if irrigation occurs within 24 h post application. Product set times beyond 2 d provide little benefit to reducing herbicide runoff.